2021
DOI: 10.3233/jad-215005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Thickness of the Anterior Cingulate Cortex as a Predictor of Amnestic-Mild Cognitive Impairment Conversion to Alzheimer’s Disease with Psychosis

Abstract: Background: A long-term follow-up study in patients with amnestic mild cognitive impairment (aMCI) is needed to elucidate the association between regional brain volume and psychopathological mechanisms of Alzheimer’s disease with psychosis (AD + P). Objective: The purpose of this study was to investigate the effect of the thickness of the angular cingulate cortex (ACC) on the risk of AD + P conversion in patients with aMCI. Methods: This was a hospital-based prospective longitudinal study including 174 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, impaired structure of ACG was also found in patients with MCI and it was paralleled with decreased performance of cognitive function, especially interference and conflict monitoring ( 58 ). The structural abnormality of ACG was identified as a predictor of cognitive impairment, which suggested that ACG played a key role in the underlying pathogenesis of cognitive impairment ( 59 ). In addition, the impaired cognitive function could be improved by mind-body exercise (movement-based mind-body intervention), which could modulate regional brain activities and structure in ACG ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired structure of ACG was also found in patients with MCI and it was paralleled with decreased performance of cognitive function, especially interference and conflict monitoring ( 58 ). The structural abnormality of ACG was identified as a predictor of cognitive impairment, which suggested that ACG played a key role in the underlying pathogenesis of cognitive impairment ( 59 ). In addition, the impaired cognitive function could be improved by mind-body exercise (movement-based mind-body intervention), which could modulate regional brain activities and structure in ACG ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimage 80, 246-262. doi: 10.1016Neuroimage 80, 246-262. doi: 10. /j.neuroimage.2013 Yan, C. G., Wang, X. D., Zuo, X. N., and Zang, Y. F. (2016). DPABI: Data Processing & Analysis for (Resting-State) Brain Imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although data are limited, the fact remains that the anterior cingulate cortex (ACC) is involved in multiple cognitive processes, including executive function (Jung et al, 2019). At the same time, the loss of ACC volume has been confirmed in patients with aMCI converted to AD (Jeong et al, 2021); On fMRI, ACC also showed degenerative changes and reduced functional activity in patients with early AD (Jung et al, 2019). Therefore, studying the role of the ACC in the development of AD is of great significance (Behrens et al, 2009;Cera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations